Dynamics of Democratic Satisfaction in Transitional Settings: Evidence from a Panel Study in Uganda. (September 2015) - Conroy-Krutz, Jeffrey; Kerr, Nicholas
How do campaigns and elections affect evaluations of democracy in transitional settings? Little research has been conducted on this topic in transitional settings, where citizens' evaluations of regime performance might be especially fluid and where popular dissatisfaction with democratic institutions could inhibit political development. Furthermore, previous studies' reliance on cross-sectional data has made it difficult to make valid causal inferences in this area. Drawing upon unique data from the 2010–2011 Uganda Campaign Panel Study, the first panel on campaign effects in Africa, we measure changes in individuals' satisfaction with democracy. We find that individuals who supported a losing presidential candidate are more likely to show decreases in satisfaction over the course of the campaign than those who supported the winner. Importantly, we find that previous political participation does not necessarily result in increases in democratic satisfaction: rather, it is associated with decreased satisfaction for losers. Finally, there is no evidence that declines in satisfaction with democracy are associated with decreased support for democracy as a regime. This study furthers understanding of political development by identifying factors that affect how citizens evaluate their political regime.